Adsorben dari Lumpur Limbah untuk Penyisihan Kromium pada Fixed Bed Column - Riyanti, Anggrika; Hadrah, Hadrah; Kasman, Monik; Marhadi, Marhadi; Samuel, Samuel (Universitas Batanghari Jambi, 2024)
Sewage sludge is a major by-product of the wastewater biological treatment process. Wastewater Treatment Plants at Palm Oil Mills (PKS) produce a lot of sewage sludge and until now it has not been optimally utilized. This study aims to examine the potential of PKS sewage sludge as an adsorbent for the removal of kromium (Cr) by the fixed bed column method. The study will also analyze the effect of recirculation on the reduction of kromium levels. The sludge was carbonized in a furnace at 300°C for 2 hours. Synthetic kromium wastewater was made at three concentrations of 2000 ppm, 3000 ppm, and 4000 ppm. The sludge adsorbent used was 100 grams which was filled into the fix bed column. Recirculation of kromium wastewater was performed 3 times. Adsorption isotherms were analyzed using Langmuir and Freundlich models. The results showed that the best removal without recirculation occurred at a kromium concentration of 3000 ppm with a removal efficiency of 48.07%. Furthermore, recirculation was carried out 3 times and resulted in varying removal values at the 1st, 2nd, and 3rd recirculation of 37.9%, 40.06% and 35.4%. The highest removal occurred in the second recirculation. The addition of recirculation led to a decrease in the sorption of chrome as the adsorbent had reached saturation point. This allows the release of kromium ions that have been adsorbed and causes the removal efficiency to decrease. A suitable adsorption isotherm model for sludge adsorbent is the Langmuir model, where the adsorption process occurs in a single layer and is homogeneous.